Light response of the chlorophyll fluorescence parameters and partitioning of absorbed light energy in wild type and npq4 mutant of Arabidopsis thaliana - Várkonyi, Zsuzsanna (Acta Biologica Szegediensis, 2005)
Photoprotective thermal dissipation of absorbed light energy is measured as non-photochemical quenching (NPQ) of chlorophyll fluorescence during exposure of plants to higher light intensities. We investigated the light response behavior of chlorophyll fluorescence and energy partitioning in PSII of npq4 mutant of Arabidopsis thaliana, which is lacking of PsbS protein, to that of the wild type plants. We found that the PsbS protein appears to function not only in thermal dissipation in light via xanthophyll pigments, but also modified the allocation pattern of excitation energy absorbed in the PSII to PSII photochemistry (P), thermal dissipation in light (DL) and excess excitation (E).